The Students’ Difficulties in Acquiring English Writing - Ade Lestari Dwi Putri; Azhary Tambusai; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
Writing skill is an essential skill which includes all knowledge and abilities to express one’s ideas through the written word. However, English writing has always been a challenge to master by the students, especially students in junior high schools. The main objective of this research is focused on finding out student’s difficulties in acquiring writing English. This study used case study with descriptive qualitative research. About 26 students are as the participants of the research. The data gained through document analysis, questioners and interview. The result indicates students had a significant problem in writing English. The findings revealed that the most significant problems are because of their lack of vocabulary mastery and language used. They assumed that they had limited knowledge in constructing sentence grammatically and also their lack of vocabulary mastery made them felt confused in choosing the word. Besides, they also were not interested in English.